Pengaruh Reformasi Internal TNI Terhadap Profesionalime Aparat Teritorial dan Implikasinya Terhadap Ketahanan Wilayah = The Influence of TNI Reform towards the Professionalism of Territorial Apparatus and Its Implication - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Along with the movement of national reform, TNI (Indonesian Armed Forces) has realized the need to carry out an internal reform. TNT's internal reform has become an awareness and commitment of Indonesian Armed Forces to actively give shape to a nation's life which is expected to be more advance, modern and democratic as well as to create TNI and TNI 's soldiers to be more professional in conducting their duties. The purpose of this research is to know the response given by territorial apparatus in dealing with TNI 's internal reformation, and the demand of territorial apparatus' professionalism, also to find out the influence and relation between the variable, which are TNI Internal Reform, Territorial Apparatus Professionalism and Regional Resilience. The population of the study is all the members of Kodim 0501 Central Jakarta and its sub-units, and the sample is all members or territorial apparatus of the Koramil Command of the Kodim 0501 Central Jakarta, and the reason is that Koramil staffs are the front liners in carrying out the territorial tasks. The research is a descriptive qualitative study and the techniques used to collect data are interview, participant observation, document analysis, and group discussion. The analysis used are data reduction, data display and summarizing. Based on the analysis of the data it shows that the response reflected by the territorial staffs towards TNI internal reformation and the demand of professionalism is very positive. Besides, this study also shows that the relation between TNT's internal reform and region resilience has taken place indirectly since the territorial apparatus professionalism has been included as a 'between' variable. The influence of TNI internal reform towards the professionalism of territorial members has happened directly. The influence